The prevalence and evidence-based management of needle fear in adults with chronic disease: A scoping review. - Emily Duncanson; Richard K Le Leu; Lisa Shanahan; Luke Macauley; Paul N Bennett; Rick Weichula; Stephen McDonald; Anne L J Burke; Kathryn L Collins; Anna Chur-Hansen; Shilpanjali Jesudason (PLoS ONE)
Background Little is known about the prevalence and best management of needle fear in adults with chronic disease, who may experience frequent and long-term exposure to needles for lifesaving therapies such as renal dialysis and cancer treatment. Identifying interventions that assist in management of needle fear and associated distress is essential to support these patients with repeated needle and cannula exposure. Method We followed the PRISMA methodology for scoping reviews and systematically searched PsychINFO, PubMed (MEDLINE), ProQuest, Embase and grey literature and reference lists between 1989 and October 2020 for articles related to needle discomfort, distress, anxiety, fear or phobia. The following chronic diseases were included: arthritis, asthma, chronic back pain, cancer, cardiovascular disease, chronic obstructive pulmonary disease, diabetes, and mental illness, or kidney failure. Literature concerning dentistry, vaccination, intravenous drug users and paediatric populations were excluded. Results We identified 32 papers reporting prevalence (n = 24), management (n = 5) or both (n = 3). Needle fear prevalence varied in disease cohorts: 17-52% (cancer), 25-47% (chronic kidney disease) and 0.2-80% (diabetes). Assessment methods varied across studies. Management strategies had poor evidence-base, but included needle-specific education, decorated devices, cognitive-behavioural stress management techniques, distraction, and changing the therapy environment or modality. Conclusion Although needle fear is common there is a paucity of evidence regarding interventions to address it among adults living with chronic disease. This scoping review has highlighted the need for improved identification of needle fear in adults and development of interventions are required for these cohorts.